The properties of hydroxyapatite ceramic coatings produced by plasma electrolytic oxidation - Adeleke S.A.; Ramesh S.; Bushroa A.R.; Ching Y.C.; Sopyan I.; Maleque M.A.; Krishnasamy S.; Chandran H.; Misran H.; Sutharsini U. (Elsevier Ltd, 2023)
Aluminum alloys; Calcium; Calcium phosphate; Ceramic materials; Electrolysis; Electrolytes; Hydroxyapatite; Medical applications; Oxidation; Phosphate coatings; Sodium compounds; Surface roughness; Ternary alloys; Titanium alloys; Vanadium alloys; Adhesive strength; Biomedical applications; Coating characteristics; Electrolyte solutions; Hydroxyapatite ceramics; Hydroxyapatite coating; Inverse relationship; Plasma electrolytic oxidation; Ceramic coatings